Affective and interpersonal psychopathic traits associated with reduced corpus callosum volume among male inmates – RETRACTED. Issue 8 (12th October 2018) - Anderson, Nathaniel E.; Maurer, J. Michael; Nyalakanti, Prashanth; Harenski, Keith A.; Harenski, Carla L.; Koenigs, Michael R.; Decety, Jean; Kiehl, Kent A.
Abstract: Background: Psychopathy is a personality disorder associated with severe emotional and interpersonal consequences and persistent antisocial behavior. Neurobiological models of psychopathy emphasize impairments in emotional processing, attention, and integration of information across large-scale neural networks in the brain. One of the largest integrative hubs in the brain is the corpus callosum (CC) – a large white matter structure that connects the two cerebral hemispheres. Method: The current study examines CC volume, measured via Freesurfer parcellation, in a large sample ( n = 495) of incarcerated men who were assessed for psychopathic traits using the Hare Psychopathy Checklist-Revised (PCL-R). Results: Psychopathy was associated with reduced volume across all five sub-regions of the CC. These relationships were primarily driven by the affective/interpersonal elements of psychopathy (PCL-R Factor 1), as no significant associations were found between the CC and the lifestyle/antisocial traits of psychopathy. The observed effects were not attributable to differences in substance use severity, age, IQ, or total brain volume. Conclusions: These findings align with suggestions that core psychopathic traits may be fostered by reduced integrative capacity across large-scale networks in the brain.